Tourism-Led Growth Hypothesis in Malaysia: Evidence Based Upon Regime Shift Cointegration and Time-Varying Granger Causality Techniques - Tang, Chor Foon; Tan, Eu Chye (Taylor & Francis, 2015)
This article examines the tourism-led growth (TLG) hypothesis in Malaysia based upon quarterly data from 1991:Q1 to 2014:Q1. The Johansen-Juselius cointegration and the regime shift cointegration tests consistently show evidence of cointegration. In addition, we find evidence of unidirectional causality from tourism to economic growth in Malaysia. Furthermore, the rolling Granger causality test confirms that the TLG hypothesis is generally valid and stable in Malaysia. Therefore, tourism is an effective long-term engine of growth. Policies to promote tourism would effectively invigorate Malaysia's long-term economic growth and development in Malaysia.